IMPLEMENTATION OF SYSTEM POINT IN IMPLEMENTATION OF EDUCATION IN MAN 2 MODELS BANJARMASIN (REVIEW IN THE PERSPECTIVE OF GUIDANCE AND COUNSELING) - Haderani, Drs (Universitas Islam Negeri Antasari Banajarmasin, 2017)
Problems facing the school is juvenile delinquency. Juvenile delinquency is so alarming cause of school MAN 2 Model Banjarmasin implement the system implementation point towards the students. With the hope that students be disciplined and strive to obey school rules at school are also at home. Peneitian This is a case study at MAN 2 Banjarmasin Model. Implementation of the system implementation point at MAN 2 Banjarmasin Model makes the students discipline, abide by the rules and deliver successful students when he graduated from school.